2017
DOI: 10.1002/cncr.31141
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of prostate cancer screening between the ages of 55 and 69 years followed by active surveillance

Abstract: Prostate-specific antigen-based prostate cancer screening in the United States between the ages of 55 and 69 years, as recommended by the USPSTF, may be cost-effective at a $100,000 threshold but only with a quadrennial screening frequency and with AS offered to all low-risk men. Cancer 2018;124:507-13. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
(117 reference statements)
1
7
0
Order By: Relevance
“…Results from a recent cost-effectiveness study modelled for the US suggested that screening between the ages of 55 and 69 years combined with active surveillance for low risk men could only be cost-effective at a $100 000 threshold if the screening frequency remains low (every four years) and active surveillance is offered to all men with low risk prostate cancer (that is, Gleason score ≤6 and stage ≤T2a). Strategies with shorter screening intervals or in which immediate treatment is offered to all men were not cost-effective 42. Although the Rapid Recommendations panel focused on the patients’ priorities rather than those of society, our recommendation is compatible with these findings.…”
Section: Understanding the Recommendationsupporting
confidence: 54%
“…Results from a recent cost-effectiveness study modelled for the US suggested that screening between the ages of 55 and 69 years combined with active surveillance for low risk men could only be cost-effective at a $100 000 threshold if the screening frequency remains low (every four years) and active surveillance is offered to all men with low risk prostate cancer (that is, Gleason score ≤6 and stage ≤T2a). Strategies with shorter screening intervals or in which immediate treatment is offered to all men were not cost-effective 42. Although the Rapid Recommendations panel focused on the patients’ priorities rather than those of society, our recommendation is compatible with these findings.…”
Section: Understanding the Recommendationsupporting
confidence: 54%
“…In this context, de Carvalho et al have explored the efficacy of PSA screening for prostate cancer in the United States from a public health perspective. They have assumed that $100,000 per quality‐adjusted life‐year saved is an appropriate standard for measuring the value of a test from a public health perspective.…”
mentioning
confidence: 99%
“…14 This statement is under reconsideration for men aged 55 to 69 years, who are advised to discuss this controversy with their primary care physician. 15 In this context, de Carvalho et al 16 have explored the efficacy of PSA screening for prostate cancer in the United States from a public health perspective. They have assumed that $100,000 per quality-adjusted life-year saved is an appropriate standard for measuring the value of a test from a public health perspective.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…64 Results of one study found it would be cost-effective if offered every 4 years and only if those with low-grade cancers identified on screening were followed with active surveillance. 65 LCDs, and 2 LCDs expected to become final in early 2020. Table 2 breaks down the coverage.…”
Section: Cost-effectiveness Of Screeningmentioning
confidence: 99%